Harnessing Amino Acids as Dual Synthons: I₂–DMSO/FeCl3-Promoted [3+2+1] Cyclization for Pyrazolo[3,4-d]pyrimidine Synthesis - Song, Yu-Man; Chen, Ting; Wang, Li-Sheng; Zhou, You; Tang, Yong-Xing; Wu, Chun-Yan; Wu, Yan-Dong; Xiang, Jia-Chen; Wu, An-Xin (Synthesis, 2025)
The synthesis of pyrazolopyrimidine has attracted considerable attention as its nitrogen-atom-rich bicyclic backbone exhibits diverse bioactivities. We report a facile and straightforward synthesis of 4,6-disubstituted pyrazolo[3,4-d]pyrimidine from α-amino acids and 5-aminopyrazole. This unprecedented transformation is enabled by I2–DMSO reagent combination and facilitated by FeCl3. A domino sequence involving I₂-mediated Strecker degradation of amino acids followed by [3+2+1] cyclization is proposed as the reaction mechanism. Two electronically distinct intermediates derived from amino acid fragmentation act as C1N1 and C1 synthons, respectively, and concurrently participate in the pyrimidine ring cyclization.
Keywords: Pyrazolo[3,4-d]pyrimidine; Amino acids; Domino reaction; Strecker degradation; Cyclizations